Pengaruh Leverage dan Transfer Pricing terhadap Tax Avoidance pada Perusahaan Pertambangan Batu Bara yang Terdaftar di BEI Periode 2019-2022 - Bonita Roida Masliana Manullang; Marthinus Ismail (VISA: Journal of Vision and Ideas, 2024)
This research is intended to explore whether leverage (debt) and transfer pricing have a significant impact on tax avoidance practices. The secondary data used comes from the annual financial reports of companies in the mining sector, especially the coal subsector, which have been collected from the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The purposive sampling method was applied in this research. The test results show that leverage has a significant influence on tax avoidance with a value of 0.003. On the other hand, transfer pricing does not show a significant impact on tax avoidance, with a value of 0.339. Leverage and transfer pricing, when considered as different variables, have a significant impact on tax avoidance with a value of 0.005.